Pengaruh Perataan Laba dan Ukuran Perusahaan terhadap Reaksi Pasar pada Perusahaan Pertambangan - Febi Tamu Rambu Duka; Yohana Febiani Angi; Eve Ida Malau (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of income smoothing and firm size on market reaction. The research was conducted on mining companies listed on the Indonesia Stock Exchange for the period 2018–2023. This study employs a quantitative approach with documentation as the data collection technique. The sample was selected using a purposive sampling method. The total sample consists of 14 companies over a period of 6 years, resulting in 84 observations, focusing on the coal and metal mineral subsectors. The data were analyzed using panel data regression, while the classical assumption tests used were multicollinearity and heteroscedasticity tests. The results of this study indicate that, partially, firm size has a negative and significant effect on market reaction, while income smoothing has no effect on market reaction. Additionally, the simultaneous test shows that income smoothing and firm size have a joint effect on market reaction.